Petrochemical industry in Nigeria: a performance appraisal - Eti, Mark C.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2004)
For any country, having a large indigenous petrochemical-producing industry tends to lead to raised prosperity, improved average standard-of-living for the population and the introduction of associated modern-technology locally. However, such benefits in Nigeria have as yet not been forthcoming to significant extents. This project reviews what needs to be done in the industry to achieve these desired improvements.